Dose Calibrator Linearity Testing: Radioisotope 99mTc or 18F? An Alternative for Reducing Costs in Nuclear Medicine Quality Control - José Willegaignon; Marcelo Sapienza; George Coura-Filho; Alexandre Garcez; Carlos Alves; Marissa Cardona; Ricardo Gutterres; Carlos Buchpiguel (World Journal of Nuclear Medicine)
Dose calibrator linearity testing is indispensable for evaluating the capacity of this equipment in measuring radioisotope activities at different magnitudes, a fundamental aspect of the daily routine of a nuclear medicine department, and with an impact on patient exposure. The main aims of this study were to evaluate the feasibility of substituting the radioisotope Fluorine-18 ( 18 F) with Technetium-99m ( 99m Tc) in this test, and to indicate it with the lowest operational cost. The test was applied with sources of 99m Tc (62 GBq) and 18 F (12 GBq), the activities of which were measured at different times, with the equipment preadjusted to measuring sources of 99m Tc, 18 F, Gallium-67 ( 67 Ga), and Iodine-131 ( 131 I). Over time, the average deviation between measured and expected activities from 99m Tc and 18 F were, respectively, 0.56 (±1.79)% and 0.92 (±1.19)%. The average ratios for 99 m Tc source experimental activity, when measured with the equipment adjusted for measuring 18 F, 67 Ga, and 131 I sources, in real values, were, respectively, 3.42 (±0.06), 1.45 (±0.03), and 1.13 (±0.02), and those for the 18 F source experimental activity, measured through adjustments of 99m Tc, 67 Ga, and 131 I, were, respectively, 0.295 (±0.004), 0.335 (±0.007), and 0.426 (±0.006). The adjustment of a simple exponential function for describing 99m Tc and 18 F experimental activities facilitated the calculation of the physical half-lives of the radioisotopes, with a difference of about 1% in relation to the values described in the literature. Linearity test results, when using 99m Tc, through being compatible with those acquired with 18 F, imply the possibility of using both radioisotopes during linearity testing. Nevertheless, this information, along with the high potential of exposure and the high cost of 18 F, implies that 99m Tc should preferably be employed for linearity testing in clinics that normally use 18 F, without the risk of prejudicing either the procedure itself or the guarantee of a high-quality nuclear medicine service.